Evaluation and management of pain in geriatric patients who were diagnosed in Emergency Department - Rybojad, Beata; Chudzik, Robert; Mendrek-Sim, Magdalena; Pawelec, Sławomir; Matuszewski, Piotr; Piróg, Paweł; Rybojad, Paweł (Journal of Education, Health and Sport, 2019)
Introduction and purpose of the work. Pain is one of the most common causes of medical rescue teams’ callings. Most of the cases are solved at patients’ homes. Some problems presented by geriatric patients are too difficult to be evaluated at home and need to be admitted to hospitals’ emergency departments(ED) for further diagnosis. Geriatric patients are often burdened with multiorgan dysfunctions which can cause pain. This problem in senior population is often overlooked or underestimated Material and method. Survey was conducted among 100 patients after 65 years of age who were admitted to ED because of pain. Location, the intensity of pain before and after application of analgesia, vital signs( heart rate, blood pressure, the number of breaths, temperature), previously administered pain killers and sociodemographic factors were evaluated and noted Results. Women predominated in the study group as well as the patients with posttraumatic pain (mostly fall from the same height). Forty five percent of patients took a painkiller at home. Preliminary average rating of pain numeric scale (NRS) was 7.49 points. Respondents who received painkillers before coming to the ED, felt more severe pain than those who did not take medications (NRS 7.93 vs. 7.41). Thirty minutes after application of analgesic pain intensity averaged 3.74 points.Conclusions. Pain is a common cause among elderly patients who report to ED, despite previously adopted analgesics. It remains underestimated in prehospital care and needs special attention in emergency departments.